In vivo evaluation of [18F]FECIMBI-36, an agonist 5-HT2A/2C receptor PET radioligand in nonhuman primate. Issue 1 (1st January 2017) - Prabhakaran, Jaya; Solingapuram Sai, Kiran Kumar; Zanderigo, Francesca; Rubin-Falcone, Harry; Jorgensen, Matthew J.; Kaplan, Jay R.; Tooke, Katharine I.; Mintz, Akiva; Mann, J. John; Kumar, J.S. Dileep
Graphical abstract: Abstract: We recently reported the radiosynthesis and in vitro evaluation of [ 18 F]-2-(4-bromo-2, 5-dimethoxyphenyl)- N -(2-(2-fluoroethoxy)benzyl)ethanamine, ([ 18 F]FECIMBI-36) or ([ 18 F]1 ), an agonist radioligand for 5HT2A/2C receptors in postmortem samples of human brain. Herein we describe the in vivo evaluation of [ 18 F]FECIMBI-36 in vervet/African green monkeys by PET imaging. PET images show that [ 18 F]FECIMBI-36 penetrates the blood-brain barrier and a low retention of radioactivity is observed in monkey brain. Although the time activity curves indicate a somehow heterogeneous distribution of the radioligand in the brain, the low level of [ 18 F]FECIMBI-36 in brain may limit the use of this tracer for quantification of 5-HT2A/2C receptors by PET.